9x+63=-1

Simple and best practice solution for 9x+63=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+63=-1 equation:


Simplifying
9x + 63 = -1

Reorder the terms:
63 + 9x = -1

Solving
63 + 9x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-63' to each side of the equation.
63 + -63 + 9x = -1 + -63

Combine like terms: 63 + -63 = 0
0 + 9x = -1 + -63
9x = -1 + -63

Combine like terms: -1 + -63 = -64
9x = -64

Divide each side by '9'.
x = -7.111111111

Simplifying
x = -7.111111111

See similar equations:

| -2x-5.8=12.2 | | s=rx+tx | | 0.004=0.2 | | y+.666=4.75 | | W/4=88 | | 48.8=0.307t+50.1 | | 62z-(33z-38)= | | -6=3y+x | | 9x^5=36x^3 | | v/-6=2=-1 | | 5=2v^2 | | 4+-7x=1+-6x | | 11x^2+4x+5= | | 3/2x=3x/8 | | -420=30(-2b) | | 47=-7-3p | | 0.5-4forx=14.5 | | -5x+43=8 | | 1500+4p=1700+2p | | 6(m-19)=55/12 | | 0.5(x+200)=0.57x-425 | | 3-2(x+2)=-7x-21 | | 6x^2+30x-38=0 | | 5p^2+12=-23p | | 2.18=[(4x+1)*.12]+.10x | | -4(z+4)+11=6z+35 | | t^2-18t+60.75= | | 5(7x+3)=15 | | -(7-4b)=16b+17 | | V^3-v^2-16v=-32 | | 4x+2+5x-5=180 | | 2x-9+6x=12x+1+x |

Equations solver categories